Image of social studies at Google - (:unkn) unknown (My University, 2012)
Social Studies Course is a lecture that ensures the students to recognize their society and the world, to involve into the social life actively towards the solution of the problems they have faced with in this respect. However, the researches indicate that this course is one of the least favorite courses by the students. Although there are various reasons for the fact that the status of social studies is low among the students, it is also important how the content of the course is reflected to them. It is a common knowledge that in 21 st century, the students spend most of their time on computer and internet. As well as they explore the facts those are challenging and within their field of interest, the students also do their homework, which is asked from them, through internet. Therefore, the image of social studies, that is introduced them via internet, comes into prominence. When the permanence and effect of the images on the human memory is regarded, the said images gain more value. Also, the images of social studies over the internet are important with respect to reflect the point of view towards this course. In this respect, within the scope of document analysis in this research, by making restriction from the detailed search option of the Google search motor, 300 visual images those are involved under the headlines of "social studies" in United States of America and "social studies" in Turkey, have been subjected to analysis. As the result of the research, it has been recognized that mostly geographical aspects of the social studies are brought into prominence over the images, and subjects and interdisciplinary structures those are included in social studies have not been reflected so much. © The Turkish Online Journal of Educational Technology.